Paediatric intensive care nursing - Crawford, Doreen; Dixon, Michaela (Wiley-Blackwell, 2012)
Paediatric Intensive Care Nursing is structured in four user-friendly sections.The first section looks at the general background of paediatric intensive care Section two employs a systems approach, with each chapter focusing on a specific disease and following the same framework